Improving academic achievement through transformational leadership with a mediating role of teacher performance and academic service quality (Case Study Of SMK YATPI Godong Students 2024/2025 Academic Year) - Rika Yulia Mustika; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2025)
Background: The academic achievement of students at SMK YATPI Godong has declined, influenced by internal factors such as the school environment, the quality of academic services, and learning motivation. Transformational leadership plays a crucial role, through teacher performance and the quality of academic services, in supporting improved student academic achievement. Purpose: This study aims to analyze the influence of transformational leadership on teacher performance and academic service quality, examine the influence of teacher performance and academic service quality on student academic achievement, and investigate the mediating roles of teacher performance and academic service quality in the relationship between transformational leadership and student academic achievement. Method: This quantitative study used a survey method and SEM-PLS analysis, with 83 randomly selected 12th-grade students of SMK YATPI Godong (2024/2025) as the sample. Results: The results show that all hypotheses were accepted: transformational leadership positively affects teacher performance and academic service quality, which in turn positively influence student academic achievement. Both teacher performance and academic service quality also act as significant mediators in this relationship. Conclusion: Transformational leadership can improve students' academic achievement through the mediating role of teacher performance and the quality of academic services. Suggestion: This research is limited to the educational context, so it is recommended that further studies include non-educational sectors and consider additional variables such as motivation and job satisfaction to enrich the understanding of the factors that influence performance and achievement. Keywords: Transformational Leadership, Teacher Performance, Academic Service Quality, Academic Achievement.